DEVELOPMENT OF SUSTAINED RELEASE MICRO/NANO PARTICLES USING DIFFERENT SOLVENT EMULSIFICATION TECHNIQUES: A REVIEW - J.B. NAIK; A.B. LOKHANDE; S. MISHRA; R.D. KULKARNI (International Journal of Pharma and Bio Sciences, 2012)
Solvent extraction/evaporation, solvent diffusion/evaporation or any modification in the basic principle of the emulsification technique produces the drug loaded sustained release micro or nanoparticles of desired properties. For understanding the basic principles of these techniques, it is essential for the development of desired objectives. Emulsification is the only step where we can disrupt the size of droplets by applying external energies like high pressure, high speed, and sonication individually or alternatively. Solidification of the drop can be controlled by rate of evaporation, extraction or diffusion. Physical as well as chemical factors can affect final results of size, encapsulation efficiency and drug release pattern. These techniques are simple at lab level, economic, robust, and well controlled methods which also give preliminary idea about the controlled factors and parameters required for the production at large scale.